Lifestyle interventions for knee pain in overweight and obese adults aged ≥45: economic evaluation of randomised controlled trial. (18th August 2009) - Barton, Garry R; Sach, Tracey H; Jenkinson, Claire; Doherty, Michael; Avery, Anthony J; Muir, Kenneth R
Abstract : Objective To estimate the cost effectiveness of four different lifestyle interventions for knee pain. Design Cost utility analysis of randomised controlled trial. Setting Five general practices in the United Kingdom. Participants 389 adults aged ≥45 with self reported knee pain and body mass index (BMI) ≥28. Interventions Dietary intervention plus quadriceps strengthening exercises, dietary intervention, quadriceps strengthening exercises, and leaflet provision. Participants received home visits over a two year period. Main outcome measure Incremental cost per quality adjusted life year (QALY) gained over two years from a health service perspective. Results Advice leaflet was associated with a mean change in cost of −£31, and a mean QALY gain of 0.085. Both strengthening exercises and dietary intervention were more effective (0.090 and 0.133 mean QALY gain, respectively) but were not cost effective. Dietary intervention plus strengthening exercises had a mean cost of £647 and a mean QALY gain of 0.147 and was estimated to have an incremental cost of £10 469 per QALY gain (relative to leaflet provision), and a 23.1% probability of being cost effective at a £20 000/QALY threshold. Conclusion Dietary intervention plus strengthening exercises was estimated to be cost effective for individuals with knee pain, but with a large level of uncertainty. Trial registration ISRCTN93206785 .